A Comparison of Cost and Reward Procedures With Interdependent Group Contingencies. (January 2017) - Lee, Kathryn; Penrod, Becky; Price, Jenifer N.
The present study evaluated the effectiveness of two variations of a token economy for reducing disruptive behavior within a general education classroom. One variation involved a group contingency in which tokens were removed contingent on disruptive behavior (response cost), and the other variation involved a group contingency in which tokens were gained according to a differential reinforcement of other behavior schedule. Two elementary school teachers and their students participated. Results indicated that both procedures were effective in reducing the overall number of students disrupting; however, both teachers and students indicated a greater preference for the response cost condition. Implications for the use of these behavior management strategies in the classroom are discussed in terms of effectiveness and ease of implementation.